Análise da fluência de leitura em pessoas com síndrome de Down: resultados do teste Cloze (Analysis of reading fluency in people with Down syndrome: Cloze test results) - Oliveira, Marian (2022)
We aim to investigate the reading fluency of people with Down syndrome (DS) using, to this end, the Cloze test (TAYLOR, 1953; KLEIMAN, 1989). Our hypothesis is that the specificities of the syndrome, such as the delay of cognition and language and compromised language, important features of text processing, will jeopardize the reading fluency and, therefore, the comprehension of texts. Three people with DS participated in this study and were submitted to three Cloze tests: rigid (TAYLOR, 1953), Rational lexical major and Rational lexical minor (KLEIMAN, 1989). The test consists in the cloze of a text to be recovered by the reader. Our results show that the three participants achieved low scores in the three tests, mostly in the Rational lexical minor, which highlights low reading fluency and, therefore, compromises the text comprehension.